THE PSYCHOLOGICAL IMPACT OF CHANGING HABITS IN CONTEMPORARY COMMUNICATION ON EDUCATION PROCESSES - Griskevica, Inguna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Education is beginning to undergo enormous change due to changes in communication habits driven by the widespread availability of digital technology. Research has found significant differences between generations that recently inhabited our society in relationships with digital communication. This semi-structured qualitative pilot study was designed as research to determine what differences existed between generations in education settings surrounding their preferred communication methods. The research for this study framed around the following three questions: (a) Are there differences in preferred methods of communication-based on generational classification? (b) Is there any difference in the use of technology as a socialization instrument between generations? (c) Is there a difference in the perceived quality of intermediate and indirect communication? A focused semi-structured interview created to determine how much of the daytime different generations spend on intermediate and indirect communication and how the quality is perceived. The results of the study from 450 samples from three generations demonstrate differences between the students and teacher perception of communication.